Health, Wealth and Happiness: Why pursue a Higher Education? - Joop Hartog; Hessel Oosterbeek (Tinbergen Institute, 1997)
We explore the effect of schooling on health, wealth and happiness for a cohort of Dutch individuals born around 1940. We also use observations on childhood IQ and family background. The most fortunate group is the group with a non-vocational intermediate level education: they score highest on health, wealth and happiness. We find that IQ affects health, but not wealth or happiness. Family background level increases wealth, but neither health nor happiness. With a father who worked independently, health, wealth and happiness are higher.Women are a miracle: compared to men, they are less wealthy, equally healthy but they are definitely happier.
Keywords: 330